Characterization of Inflammation in Delayed Cortical Transplantation - Ballout, Nissrine; Rochelle, Tristan; Brot, Sebastien; Bonnet, Marie-Laure; Francheteau, Maureen; Prestoz, Laetitia; Zibara, Kazem; Gaillard, Afsaneh (Frontiers in Molecular Neuroscience, 2019)
We previously reported that embryonic motor cortical neurons transplanted one-week after lesions in the adult mouse motor cortex significantly enhances graft vascularization, survival, and proliferation of grafted cells, the density of projections developed by grafted neurons and improves functional repair and recovery. The purpose of the present study is to understand the extent to which post-traumatic inflammation following cortical lesion could influence the survival of grafted neurons and the development of their projections to target brain regions and conversely how transplanted cells can modulate host inflammation. For this, embryonic motor cortical tissue was grafted either immediately or with a one-week delay into the lesioned motor cortex of adult mice. Immunohistochemistry analysis was performed to determine the density and cell morphology of resident and peripheral infiltrating immune cells. Then, in-situ hybridization was performed to analyze the distribution and temporal mRNA expression pattern of pro-inflammatory or anti-inflammatory cytokines following cortical lesion. In parallel, we analyzed the protein expression of both M1- and M2-associated markers to study the M1/M2 balance switch. We have shown that one-week after the lesion, the number of astrocytes, microglia, oligodendrocytes, and CD45+ cells was significantly increased along with characteristics of M2 microglia phenotype. Interestingly, the majority of microglia co-expressed TGF-β1, an anti-inflammatory cytokine, supporting the hypothesis that microglial activation is also neuroprotective. Our results suggest that the modulation of post-traumatic inflammation one-week after cortical lesion might be implicated in the improvement of graft vascularization, survival, and density of projections developed by grafted neurons.